Evaluation of Crambe abyssinica Hochst. ex R.E.Fr. (Brassicaceae) for arsenic removal and speciation changes in an Oxisol - Silva, Silmara Costa (2017)
Arsenic (As) is widely distributed around the world. Despite its natural occurrence in some sites, As contamination is a concern for human health and the environment. Phytoremediation is an alternative to decontaminate As contaminated soils, by using hyperaccumulators or tolerant plants. This work aimed to evaluate the potential of Crambe abyssinica for As phytoremediation in response to different As and phosphorus (P) amendments in soil and to map the spatial distribution and speciation of As in As(III)- or As(V)-treated soil, the rhizosphere and plant parts of Crambe. Two different experiments were carried out. For the first experiment, a sandy Oxisol from the Brazilian Cerrado was incubated with P (NH 4 H 2 PO 4 ) and As (As 2 O 3 ) dissolved in 1 mol KOH L -1 and oxidized to As(V), both at doses of 0, 50, 100, 150 or 200 mg dm -3 in a factorial experiment design. Three Crambe seedlings, previously germinated for 7 days, were transplanted to each greenhouse pot and allowed to grow for 105 days to the seed-production stage. Arsenic uptake by Crambe was evaluated, along with biomass production, As concentrations in roots, stems, leaves, and seeds; translocation and bioaccumulation factors; and seed germination. For the second experiment, the same type of soil from the first experiment was used for Crambe growth. To guarantee visualization of roots during the experiment, plants were cultivated in chambers in which the roots grew between two acrylic plates separated by 5 mm. The soil received 10.7 mmol L -1 solution of As(III) and As(V) separately, composing two different treatments. Plants were cultivated in a greenhouse for 20 days. For arsenic spatial distribution and speciation, samples were analyzed at the Synchrotron X-Ray Fluorescence beamline (SXRF) at the Brazilian Synchrotron Laboratory (LNLS), Campinas, SP. Samples were separated into leaves and the soil-rhizosphere system. The µ-SXRF analyses were performed using a white beam. After mapping an area of each sample, locations with higher As fluorescence intensity (hotspots) were identified, and µ-XANES spectra were collected using a monochromatic beam to identify arsenic species in the root-rhizosphere-soil continuum. After data collection, plants were harvested, separated into leaves and roots for trifluoracetic acid (TFA) extraction and speciation by HPLC-AFS. In general, we observed that biomass production decreased with increasing As for all P doses greater than the control treatments (without P and As addition). Arsenic concentration in plants increased with increasing P addition, reaching 759 mg kg -1 of As in the As150/P200 treatment (150 mg As dm -3 + 200 mg P dm -3 ). Crambe grown in As-treated soils produced viable seeds with germination rates between 60 and 95 %, and containing less than 2 % of the total As in the plant, even for the highest As dose (As200). Our results also suggest that As is located mainly in veins of Crambe abyssinica leaves and most of the As in leaves is arsenite [As(III)]. In the root-rhizosphere system, differences between arsenic species in soil and rhizosphere were found for both samples, suggesting that Crambe roots change the rhizosphere in ways that induces changes in As speciation by arsenate reduction or promoting methylation, possibly to detoxify arsenic. The best As/P treatment for As content in Crambe shoot was As100/P200, which resulted in As removal of up to 9 kg ha -1 from soil. Besides accumulating high As amounts into its tissues, Crambe abyssinica plants showed TFs (Translocation Factors) and BFs (Bioconcentration Factors) of 5.09 and 61.11, respectively, suggesting that this species is potentially useful for phytoextraction of As from contaminated soils.